Teaching power system stabilizer and proportional-integral-derivative impacts on transient condition in synchronous generator - Sugiarto Kadiman; Oni Yuliani; Trie Handayani (Bulletin of Electrical Engineering and Informatics, 2021)
Understanding the concepts based on problem solving is not an easy methodology in teaching the impact of power systems stabilizer (PSS) on transient synchronous generator using MATLAB capability. Experiments conducted in simulating sessions play an important role in this teaching. This simulation can simulate power system stability behavior with reasonable accuracy in less time. This transient phenomenon of a power system utilizing synchronous generator and modelling by fully three-phase model with changes in stator flux linkages neglected is analyzed by employed single machine infinite bus taken to the power system. Whereas a power system stabilizer which consist of a wash-out circuit, two stages of compensation, a filter unit, and a limiter, is applied to control voltage and frequency of power systems in transient condition. Proportional-integral-derivative (PID) controller tuned by Ziegler-Nichols’s method is cascaded to conventional PSS in order to enhance the response time of system while providing a better result in damping for oscillation. This gives the clear idea about PSS and PID controller impacts on transient synchronous generator and its enhancement to the students of electrical engineering program, Institut Teknologi Nasional Yogyakarta.